Cystic fibrosis (CF) care through the patients' eyes – A nationwide survey on experience and satisfaction with services using a disease-specific questionnaire. Issue 1 (January 2015) - Steinkamp, Gratiana; Stahl, Katja; Ellemunter, Helmut; Heuer, Eberhard; van Koningsbruggen-Rietschel, Silke; Busche, Melanie; Bremer, Wilhelm; Schwarz, Carsten; Patient Experience Working Group
Summary The patients' perspective is an important aspect of quality management. A newly developed disease-specific questionnaire was used to assess the patients' experiences with care provided in specialised cystic fibrosis (CF) care centres. Methods 90 CF centres in Germany were invited to participate. Centre staff collected patient consent forms and sent the patients' addresses to the study centre. The questionnaires for adults and parents had 100 and 104 items respectively, with 3–6 response categories each. Items were dichotomised into "problem scores" (PS), indicating the presence or absence (PS 0%) of a reported problem. Results 56 CF centres took part in the survey and recruited 1642 adults with CF and 1205 parents. The response rates were 74% in each group, with 1221 completed questionnaires from adults and 891 from parents. Participants reported good experiences with care. Factor analysis revealed 10 factors covering 70 items. Participants reported the best results for the factors "Physiotherapists" (PS 6%) and "Physician–Patient Relationship" (PS 9%). Factors with the highest problem scores were inpatient and outpatient "Facilities, Hygiene and Services". CF centres received reports of their own results and mean problem scores of all participating institutions. The problem scores differed considerably between CF centres. Conclusions The nation-wide CF-specific patient experience survey identified specific shortcomings which were mainly related to communication, centre organisation, and facilities. Centre staff can use the results to improve the quality of care. We suggest that patients' views should become an integral component of efforts to promote patient-centred care.